Preoperative imatinib treatment in patients with locally advanced and metastatic/recurrent gastrointestinal stromal tumors: A single-center analysis - Wang, Jian (Medicine (Baltimore), 2020)
The advent of imatinib mesylate (IM) has dramatically revolutionized the prognosis of advanced and metastatic/recurrent gastrointestinal stromal tumors (GISTs). The objective of this retrospective study is to investigate the safety and efficacy of combination of surgery following IM treatment in the management of advanced and metastatic/recurrent GISTs. We further explore the long-term clinical outcomes in these who underwent therapy of preoperative IM. Eligible patients with GISTs before the onset of the IM therapy and were periodically followed up in the outpatient clinic were included in this study. Detailed clinical and pathologic characteristics were obtained from the medical records of our institution. Univariate and multivariate regression analyses were performed to use for the evaluation of potential prognostic factors. A total of 51 patients were included in the study, of these patients, 36 patients underwent surgery and median duration of preoperative IM is 8.2months (range 3.5–85 months). Significant median tumor shrinkage rate was 29.27% (95% confidence interval 21.00%–34.00%) observed in these patients who responded to IM, and partial response and stable disease were achieved in 24 patients (47.06%) and 23 patients (45.10%), respectively, in light of the RECIST guideline (version 1.1). After the median follow-up of 43.70 months (range 14.2–131.1 months), 1- and 3-year overall survival (OS) were estimated to be 96.1% and 94.0%, respectively, and there was a significant improvement in OS for patients who received surgical intervention versus those who did not. Our study consolidates that patients were received preoperative IM therapy could shrink the size of tumors and facilitate organ-function preservation. The long-term analysis on this study supports that surgical intervention following IM therapy benefits for patients with primary advanced and recurrent or metastatic GISTs on long-term prognosis.